Software defined P2P architecture for reliable vehicular communications - Rufino, João
Vehicular networking is considered a promising and enabling technology that helps in the realization and diversification of vehicle related applications such as road traffic safety, emergency management, and infotainment. For applications such as the road traffic safety, the system has to respond in certain bounded time and ensure higher reliability. A major bottleneck of the existing architectures is the reliability and scalability that results in a considerable performance degradation. Therefore, in this paper, we proposed a software defined peer to peer (P2P) architecture for reliable vehicular communications solution that scales out overall network intelligence into the system components (Road side units, on-board units, Gateways, Control centre) and offer an unprecedented reliability, adaptability and scalability. The reliability of the communication is achieved by using redundant system components such as multiple switches and GWs links that are deployed to achieve lower communication latencies and higher packet success rates. Furthermore, higher reliability is achieved by the application of fast-failover and fast recovery techniques. The proposed architecture is implemented using Docker, and containerized ONOS and Cassandra. The obtained results show that the proposed architecture offer higher reliability by offering higher packet success rate (PSR) and smaller round trip time (RTT).